Studi Morfologi Bunga Jantan dan Serbuk Sari pada Genus Musa - Welsiliana welsiliana; Florian Mayesti Prima R. Makin; Dicky Frengky Hanas (Fakultas Pertanian, Universitas Timor, 2020)
Grouping a plant can be done by recognizing the character of the plant. One character can be seen through the difference in the morphology of flowers and pollen. The purpose of this study was to determine the form of variations in male flowers and pollen of the genus Musa which can be used as a source of taxonomic evidence. This study used 10 banana accessions analyzed by descriptive qualitative. The result showed the character difference of male banana flower morphology was more varied than the pollen morphology.